1984
DOI: 10.1111/j.1365-2389.1984.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas diffusion through soil crumbs: the effects of compaction and wetting

Abstract: Samples of 1-2 mm crumbs from a clay loam under permanent pasture were equilibrated at -5 kPa water potential then compacted to varying degrees. Gas diffusion coefficients D, (hydrogen through air), were measured immediately on compaction, again after re-equilibration at -5 kPa, then at other water contents between saturation and dryness. The relationship between diffusion coefficient and air content, E , was, as elsewhere, in two parts (dD/dE small for drainage of pores within crumbs; large for pores between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 12 publications
6
45
0
5
Order By: Relevance
“…The decrease of C and v a, th with the increase in rd implies that at a given soil-air content within intermediate soil-moisture conditions (i.e., except at high soil-air contents) the soil-gas diŠusivity increased with a decrease in bulk density. This is in agreement with Currie (1984) . Lastly, the new 2RP model predicted excellently the measured D p values on repacked Nishi-Tokyo volcanic ash soils at three diŠerent bulk densities (Fig.…”
Section: Ešects Of Soil Compaction On Gas Dišusivitysupporting
confidence: 82%
“…The decrease of C and v a, th with the increase in rd implies that at a given soil-air content within intermediate soil-moisture conditions (i.e., except at high soil-air contents) the soil-gas diŠusivity increased with a decrease in bulk density. This is in agreement with Currie (1984) . Lastly, the new 2RP model predicted excellently the measured D p values on repacked Nishi-Tokyo volcanic ash soils at three diŠerent bulk densities (Fig.…”
Section: Ešects Of Soil Compaction On Gas Dišusivitysupporting
confidence: 82%
“…This indicates that roots in the compact soil, such as hard pan layer, require a lower soil water potential (drier condition) for their favorable growth under the relatively wet environment. This result agrees with the general trends of relative diffusion coeffi cient (D/D 0 ) in a clay loam soil (Currie, 1984) and ODR in a silt loam soil (Agnew and Carrpw, 1985).…”
Section: Soil Physical Stressessupporting
confidence: 81%
“…We feel that the error lies in the coefficients used to adjust DCH4. These depend on both soil structure and moisture; Currie (1984) demonstrated that for a single soil type of varying moisture content no single relationship was satisfactory. In contrast, we are confident in our estimates for ACcH, in Equation 1 because soil CH, distributions similar to those in Fig.…”
Section: Comparison Of Information From Each Measurementioning
confidence: 99%